Baltų dvikamienių asmenvardžių kamienas gud-: ryšiai su gaud- ir kai kurie jo variantai - Sinkevičiūtė, Daiva (Baltistica, 2011)
Baltic compound proper names with gud-: variation and relationship to gaud-A survey of the Lithuanian and Old Prussian compound proper names with the stem gud- shows them to be of heterogeneous date and origin.The oldest layer (e.g. OPr. Gudewill, Lith. Gudvilas, Milgudas, Sirgudas, etc.) originated from Lith. gùsti, OPr. gudde and is found in compound names with the same components as Lithuanian, Prussian and Curonian names with gaud-. Both stems, gud- and gaud-, are in a well-established ablaut relationship. The best account of gaud- seems to be that of Leskien, with Lith. gáuti. A connection with other words denoting sounds would be secondary.A later layer are Lithuanian proper nouns with the same components as Lithuanian names with gaud- (e.g. Lith. Daugudis, Gelgudas, Gudvainis, etc.). Since the elements in combination with gud- are well attested among compound proper names, are semantically opaque, and the members of the compound names are not semantically related, gud- is also to be related to Lith. gùsti.A still later layer are names where gud- is not in variation with gaud- (e.g. Lith. Gudigirdas, Gudmintas, etc.). They may have arisen on the model of other names with gud-. Variants with gu-, gūd-, gut- (e.g. Lith. Gelguta, Gūdmantas, Gutautas, etc.) probably belong in this layer as well, as they are not in variation with gaud- and the members of the compound names are not semantically related.The most recent layer are names whose second member is either an appellative stem (e.g. Lith. Gudparakis, Gudwietys, etc.), or is taken from names of Christian origin (e.g. Lith. Gudmikas, Gudpetris, etc.). In these names gud- is related to the ethnonym gùdas, as the relationship between the members of the compounds points to origin in nicknames.
Keywords: onomastika; gud-; asmenvardžiai